Ecosystemic resilience of a temperate post-fire forest under extreme weather conditions - Blumroeder, Jeanette S.; Schmidt, Frederic; Gordon, Anat; Grosse, Stefanie; Ibisch, Pierre L. (Frontiers in Forests and Global Change, 2022)
Introduction The effects of climate change are exacerbating the fire risk in forests worldwide. Conifer plantations in particular are especially vulnerable to fire outbreaks. At the end of the extraordinarily hot and dry summer of 2018, a forest pine plantation burned in Brandenburg, NE Germany. Different forestry interventions were carried out after the fire, while one area of the damaged plantation remained untouched. Methods We investigated the resilience of the forest ecosystem and the effectiveness of different active and passive forest restoration measures during the subsequent relatively warm and dry years 2019–2021. Results One year after the fire, Populus tremula showed strong spontaneous colonization at all sites. In contrast, the majority of planted Pinus sylvestris plantlets died on the plots that had been salvage-logged after the fire. Three years after the fire, Populus tremula successfully established itself as the dominant tree species on all plots, with the highest abundance on the plot where the overstorey of the dead pines was left. Betula pendula, Salix caprea, and Pinus sylvestris showed lower abundance, with their proportion increasing with decreasing cover by dead trees. The distribution of regrowing trees is very heterogeneous across the different treatments and plots. In the clear-cut plots, the extreme microclimatic conditions expose the young trees to additional heat and drought, while the retention of deadwood measurably buffers the temperature and water stress. Discussion The resilience and adaptability of naturally regenerating forests that develop into ecosystems that are more diverse seem more promising than restoration through intervention. Apart from hampering restoration under extreme weather conditions, post-fire salvage logging contributes to soil degradation and loss of organic carbon.